2011
DOI: 10.2196/jmir.1624
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Web-based Intervention Aimed at Healthy Dietary and Physical Activity Behavior: A Randomized Controlled Trial About Users and Usage

Abstract: BackgroundRecent studies have shown the potential of Web-based interventions for changing dietary and physical activity (PA) behavior. However, the pathways of these changes are not clear. In addition, nonusage poses a threat to these interventions. Little is known of characteristics of participants that predict usage.ObjectiveIn this study we investigated the users and effect of the Healthy Weight Assistant (HWA), a Web-based intervention aimed at healthy dietary and PA behavior. We investigated the value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
101
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 50 publications
14
101
1
Order By: Relevance
“…As has been seen in prior physical activity interventions delivered through the internet, [13][14][15][16] engagement declined as the intervention progressed. Although all participants engaged in the Facebook Social Support Group, there was also a wide range of engagement with a minimum of 6 total posts to a maximum of 32 total posts.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As has been seen in prior physical activity interventions delivered through the internet, [13][14][15][16] engagement declined as the intervention progressed. Although all participants engaged in the Facebook Social Support Group, there was also a wide range of engagement with a minimum of 6 total posts to a maximum of 32 total posts.…”
Section: Discussionmentioning
confidence: 73%
“…The use of Facebook may also aid in ameliorating a frequently reported hindrance of physical activity interventions delivered through the internet which is getting and keeping participants engaged and visiting the intervention website. [12][13][14][15][16] The average Facebook user logs into Facebook 3 times per day, 17 a login rate that is 7 times higher than that seen among previous internet-based physical activity interventions. 16 The use of social media in health-promoting interventions is not new and has resulted in improvements in several aspects of health (eg, sexual health, food safety, and weight loss).…”
mentioning
confidence: 99%
“…Engagement with online or electronic pregnancy interventions has been examined only in a few studies and has been relatively low. Kelders et al 10 found that 64% of participants used their online…”
Section: Introductionmentioning
confidence: 99%
“…These were conducted in The Netherlands (2011) 98 and United States (2014). 99 They are summarized in Table 5.…”
Section: Feasibility Of Gdm Telemonitoringmentioning
confidence: 99%
“…In 2011, an RCT (n = 297) 98 was conducted in The Netherlands that investigated the predicted usage of a Web-based intervention aimed at promoting healthy diet and physical activity. In total, 297 respondents were recruited from various public sources, including advertisements in local newspapers, postings in supermarkets, and a health-related Web site.…”
Section: Feasibility Of Gdm Telemonitoringmentioning
confidence: 99%